Penentuan Nilai Hambatan dan Hambatan Jenis pada Arang Batok Kelapa dan Arang Kulit Pisang dengan Metode Eksperimen - nurhayati nurhayati (PTE FTK UIN Ar-Raniry, 2020)
Due to an application of coconut shell and cassava peel-based charcoal as an alternative material in carbon film resistors, the purpose of this study is to determine the value of both resistance and specific resistance of those materials. The fresh coconut shell and cassava peel were dried under sunlight prior to charcoal production through pyrolysis. The resulted charcoals were then grounded into powder and filtered. After that, the fine materials were inserted into a straw with a wide area of 6,07 x 10-7 m2and 1,2 x 10-4 m2 and the length of 0,03 m and 0,04 m. The results obtained that the resistance values of the coconut shell and cassava skin charcoal were 5 104 Ω to 11 104 Ω and 3 104Ω to 5 104 Ω, respectively. While the specific resistance values of those charcoals were 1,133 Ωm to 2,34 × 102 Ωm and 0,758 Ωm to 1,28 102 Ωm, respectively. In conclusion, both resistance and specific resistance values of coconut shell charcoal seem to be relatively higher than the coconut shell charcoal.